Pathological gambling: biopsychosocial approach - Kalyoncu, Ö. Ayhan; Pektaş, Özkan; Mırsal, Hasan (Journal of Dependence, 2003)
Objective: Pathological gambling is an increasing public health problem. Many mental health professionals have limited information regarding the etiology, phenomenology and treatment of this patient population. In this article, we have reviewed the literature of pathological gambling.Method: We made computerized literature search using PubMed for the years 1984 to 2003 and to the choice of articles by random.Results: There are several competing conceptualizations of pathological gambling: as an impulse control disorder, a mood disorder, an obsessive-compulsive spectrum disorder, or a non-pharmacological addiction. An alternative model of pathological gambling is as a heterogeneous disorder with different subtypes sharing certain characteristics. Both biological and psychological factors play a role in the etiology of pathological gambling. Treatment options include several medications, psychotherapies and attendance to Gamblers Anonymous, although none of them are established treatments.Conclusion: There is the need for further research in order to improve the understanding of this disorder and improve the quality of the treatments available.
Keywords: Pathological gambling; impulse control; mood disorder; obsessive-compulsive disorder; addiction